2019
DOI: 10.1093/ajcn/nqz202
|View full text |Cite
|
Sign up to set email alerts
|

The association of human milk oligosaccharides with glucose metabolism in overweight and obese pregnant women

Abstract: Background Human milk oligosaccharides (HMOs) were recently found in serum of normal-weight pregnant women, with concentrations increasing from early to mid- and late pregnancy. Whether HMOs have effects on maternal metabolism is unknown. Objectives We aimed to study the presence and changes in HMOs throughout pregnancy and assess associations with maternal glucose metabolism throughout pregnancy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 38 publications
2
34
0
1
Order By: Relevance
“…The inflammation-associated increase in serum 3=SL seems to fit with our previous study in pregnant women at risk for GDM, which is also considered an inflammatory disorder. Serum 3=SL was higher in women who later developed GDM (16). In addition, accumulating evidence points toward increased plasma sialic acid in inflammatory pathologies such as cancer, cardiovascular diseases, and type 2 diabetes (38).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The inflammation-associated increase in serum 3=SL seems to fit with our previous study in pregnant women at risk for GDM, which is also considered an inflammatory disorder. Serum 3=SL was higher in women who later developed GDM (16). In addition, accumulating evidence points toward increased plasma sialic acid in inflammatory pathologies such as cancer, cardiovascular diseases, and type 2 diabetes (38).…”
Section: Discussionmentioning
confidence: 95%
“…While some studies have investigated changes in HMOs in human milk as a consequence of PTB (34-36), their potential causal role in PTB has not yet been explored. Recently, we showed that serum HMOs change during preg-nancy (15,16) and that an individual HMO, 3=SL, may be predictive of gestational diabetes mellitus (GDM) (16). An early study on maternal urinary HMOs speculated about the importance of a balanced HMO profile in maintaining a healthy pregnancy (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, Jantscher-Krenn et al reported an association between circulating HMO concentrations during pregnancy and maternal glucose metabolism in a cohort of overweight and obese women. Interestingly, they found that including concentrations of the HMO 3 -sialyllactose (3 SL) in a model that predicted the development of gestational diabetes mellitus significantly improved the area under the curve for the model, suggesting that HMO production during pregnancy may influence maternal glucose homeostasis [17]. Given the recent findings that HMO production begins as early as 10 weeks of pregnancy [6], it is plausible to hypothesize that maternal factors during pregnancy such as hyperglycemia, hyperinsulinemia, or insulin resistance may influence HMO synthesis all the way into lactation.…”
Section: Introductionmentioning
confidence: 99%